Poly(vinylidene fluoride-hexafluoropropylene) polymer electrolyte for paper-based and flexible battery applications - Nojan Aliahmad; Sudhir Shrestha; Kody Varahramyan; Mangilal Agarwal (AIP Advances, 2016)
Paper-based batteries represent a new frontier in battery technology. However, low-flexibility and poor ionic conductivity of solid electrolytes have been major impediments in achieving practical mechanically flexible batteries. This work discuss new highly ionic conductive polymer gel electrolytes for paper-based battery applications. In this paper, we present a poly(vinylidene fluoride-hexafluoropropylene) (PVDH-HFP) porous membrane electrolyte enhanced with lithium bis(trifluoromethane sulphone)imide (LiTFSI) and lithium aluminum titanium phosphate (LATP), with an ionic conductivity of 2.1 × 10−3 S cm−1. Combining ceramic (LATP) with the gel structure of PVDF-HFP and LiTFSI ionic liquid harnesses benefits of ceramic and gel electrolytes in providing flexible electrolytes with a high ionic conductivity. In a flexibility test experiment, bending the polymer electrolyte at 90° for 20 times resulted in 14% decrease in ionic conductivity. Efforts to further improving the flexibility of the presented electrolyte are ongoing. Using this electrolyte, full-cell batteries with lithium titanium oxide (LTO) and lithium cobalt oxide (LCO) electrodes and (i) standard metallic current collectors and (ii) paper-based current collectors were fabricated and tested. The achieved specific capacities were (i) 123 mAh g−1 for standard metallic current collectors and (ii) 99.5 mAh g−1 for paper-based current collectors. Thus, the presented electrolyte has potential to become a viable candidate in paper-based and flexible battery applications. Fabrication methods, experimental procedures, and test results for the polymer gel electrolyte and batteries are presented and discussed.